3) VT = $\frac{-(b-c)^2}{(a-b)(b-c)(c-a)}+\frac{-(c-a)^2}{(a-b)(b-c)(c-a)}+\frac{-(a-b)^2}{(a-b)(b-c)(c-a)}=-\frac{(a-b)^2+(b-c)^2+(c-a)^2}{(a-b)(b-c)(c-a)}=\frac{2ab+2bc+2ca-2a^2-2b^2-2c^2}{(a-b)(b-c)(c-a)}VP=\frac{2(b-c)(c-a)+2(c-a)(a-b)+2(a-b)(b-c)}{(a-b)(b-c)(c-a)}=\frac{(2bc-2ab-2c^2+2ca)+(2ca-2bc-2a^2+2ab)+(2ab-2ca-2b^2+2bc)}{(a-b)(b-c)(c-a)}$ = VT
3) VT = $\frac{(a-c)-(a-b)}{(a-b)(a-c)}+\frac{(b-a)-(b-c)}{(b-c)(b-a)}+\frac{(c-b)-(c-a)}{(c-a)(c-b)}=\frac{1}{a-b}-\frac{1}{a-c}+\frac{1}{b-c}-\frac{1}{b-a}+\frac{1}{c-a}-\frac{1}{c-b}$ = VP